Translocator Protein TSPO (Peripheral Benzodiazepine Receptor): The Modern Story of the Ancient Preserved Protein with Ambiguous Functions - Al Mulla Hummadi, Yassir Mustafa Kamal (Iraqi Journal of Pharmaceutical Sciences, 2024)
In several tissues, including the brain, heart, blood, intestines, adrenal glands, and liver, the 18 kDa translocator protein (TSPO) was shown to be the peripheral benzodiazepine receptor. There is strong evidence that TSPO is expressed in microglial cells in the central nervous system. Five transmembrane regions are seen at the cellular level in TSPO at the contact points between the outer and inner layers of mitochondria. The cytosolic region of the complex of amino acids that binds cholesterol is where cholesterol is taken up. TSPO is found as a monomer of 18 kDa and homomultimers and homodimers. Different factors, such as cholesterol concentration and reactive oxygen species, change the multimeric structure. As a result, TSPO gains responsibility for transferring cholesterol to the mitochondrial intermembrane space, transforming it into a steroid. Additionally, TSPO appears to collaborate with other mitochondrial membrane proteins to play a part in regulating the activity of the MPTP (mitochondrial permeability transition pore) and, therefore, in the elements of apoptosis. In vivo imaging of TSPO addresses a significant test in examining brain pathology like neuroinflammatory, Alzheimer’s, and schizophrenia. Additionally, TSPO’s use as a biomarker may have important implications for developing more viable diagnostic and therapeutic approaches. The current work surveys the TSPO cellular origin and attempts to comprehend its role in various physiological and pathological conditions.